2005
DOI: 10.1269/jrr.46.37
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tocopherol-monoglucoside (TMG), a Water-soluble Glycosylated Derivate of Vitamin E, on Hematopoietic Recovery in Irradiated Mice

Abstract: A preparation of alpha-tocopherol monoglucoside (TMG) administered i.p. at a dose of 600 mg/kg immediately after whole body gamma irradiation was examined for its radioprotective efficacy towards bone marrow and peripheral blood nucleated cells. When mice received X-rays at a dose of 5,6 Gy, a marked decrease in bone marrow karyocytes and a reduction of peripheral leukocytes within the early post-irradiated period were observed. However these changes were attenuated in TMG-treated mice. Significant protection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Previous studies have shown that treatment with vitamin E increased the number of colony forming units of erythroid precursors (CFU-E), enhanced erythropoiesis and haemoglobin levels, and corrected experimentally induced anaemia in laboratory animals [20][21][22]. Our data indicate that the stimulatory effect of DT3 is not limited to erythropoiesis, but extends to leukopoiesis and megakaryopoiesis.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies have shown that treatment with vitamin E increased the number of colony forming units of erythroid precursors (CFU-E), enhanced erythropoiesis and haemoglobin levels, and corrected experimentally induced anaemia in laboratory animals [20][21][22]. Our data indicate that the stimulatory effect of DT3 is not limited to erythropoiesis, but extends to leukopoiesis and megakaryopoiesis.…”
Section: Discussionsupporting
confidence: 59%
“…After the 7th day, recovery in the leukocyte count was observed, which can be attributed to the free radical scavenging property and DNA protective ability of aryltetralin lignans and flavonoids, due to which cells were able to repair the damage induced by radiation at bone marrow level. Similarly, protection of the hemopoietic system has been reported by using tocopherol monoglucoside 18 and phytoextracts such as Adhatoda vasica, Hippophae rhamnoides, Aegle marmelos, and Syzygium cumini. 19,20 The pattern of DLC in terms of neutrophils remained unchanged for the control group.…”
Section: Discussionmentioning
confidence: 70%
“…It forms a phenoxyl radical similar to trolox upon reaction with various one-electron oxidants. TMG protected mice against TBI, protected DNA strand breaks and thymine glycol formation induced by γ-irradiation [29,30], reduced the percentage of aberrant metaphase and the number of micronucleated erythrocytes [31], and enhanced hematopoietic recovery in irradiated mice [32].…”
Section: Discussionmentioning
confidence: 99%